Mapping creativity: a historical contextualisation of emigre literature - Altabaa, Homam (2019)
Émigré artists such as Kahlil Gibran (1883-1931, Mikhail Naimy (1989-1988), Ameen Rihani (1876-1940) and Elia Abu Madi (1980-1957) have shown the world that it is feasible to surpass the historical and geographical limitations of one’s birth to reach the global highpoints of world literature. The creativity of émigré writers was shaped by the influence of the meeting of two cultures, through their travels and immigration between the Levant and the West. Thus, their creative works are closely related to and influenced by their historical realities. A deep and authentic appreciation of these works, such as The Book of Khalid, The Book of Mirdad and The Prophet can only be achieved through an examination of the biographical context of these works. A better understanding of the political, social, cultural and economic conditions of the nineteenth and twentieth centuries can only lead to a better grasp over the themes and styles of the émigré literary output. Accordingly, this research presents an overview of the historical context of the Émigré literary movement, beginning with historical backgrounds in the Levant and the United States of America. This is followed by an overview of immigration to the US at the turn of the twentieth century. The contexts of both Arabic literature and American literature at the same period is subsequently examined. Finally, the implications of the aforementioned topics on the émigré literary movement are discussed.